Clinical Effectiveness of Blended CBT Compared to Face-to-Face CBT: a Randomised Controlled Non-Inferiority Trial (Preprint) - Kim Mathiasen; Tonny E. Andersen; Mia Beck Lichtenstein; Heleen Riper; Annet Kleiboer; Kirsten Kaya Roessler (2022)
BACKGROUND Background: Internet-based cognitive behavioural therapy (iCBT) has been demonstrated to be cost- and clinically effective. There is a need, however, for increased therapist contact for some patient groups. Combining iCBT with traditional face-to-face consultations in a blended format may produce a new treatment format (B-CBT) with multiple benefits from both traditional CBT and iCBT such as individual adaptation, lower costs than traditional therapy, wide geographical and temporal availability, and possibly lower threshold to implementation. OBJECTIVE The primary aim of the present study is to compare directly the clinical effectiveness of B-CBT with face-to-face CBT (FtF-CBT) for adult major depressive disorder. METHODS Methods: The study was designed as a two-arm randomised controlled non-inferiority trial comparing B-CBT for adult depression with treatment as usual (TAU). In the blended condition six sessions of FtF-CBT was alternated with six to eight online modules. TAU comprised twelve sessions of FtF-CBT. All participants were eighteen years of age or older and met the diagnostic criteria for major depressive disorder according to the Diagnostic and Statistical Manual of Mental disorders 4th edition (DSM-IV). Participants were randomised on an individual level by a researcher not involved in the project. At baseline, demographic characteristics (age, gender, marital status, highest level of education, occupational status), current other treatment, and treatment preference was recorded. The primary outcome was change in depression severity on the patient-health questionnaire-9 (PHQ-9). Secondary analyses included questionnaires measuring client satisfaction (CSQ-8), patient expectancy (CEQ), and working (WAI and TAI). The primary outcome was analysed by applying maximum likelihood estimation of a mixed effects model including all available data from baseline, weekly measures, three-, and six-months follow-up. RESULTS Results: A total of N=76 were randomised, n=38 allocated to each treatment, age ranged from 18 to 71 years (SD=13.96) with 73.7% (n=56) female. Attrition rate was 19.7% (n=15), less from the FtF-CBT group (15.8%, n=6) than the B-CBT group (23.7%, n=9). Completion was defined as having completed >= 9 sessions, which was achieved by n=53 (69.7%) almost equally distributed between the groups (nFtF-CBT=27 (71.1%), nB-CBT= 26 (68.4%)). The mean change in depression severity from baseline to twelve-months follow-up was 11.38 in the FtF-CBT group and 8.10 in the B-CBT group. At six months, the mean difference was a mere 0.17 point on the PHQ-9. The primary analyses confirmed large and significant within group reductions in both groups (FtF-CBT: ß = -0.03, SE = 0.00, P < .001; B-CBT: ß = -0.02, SE = 0.00, P < .001). There was a very small but significant interaction effect between groups (ß = 0.01, SE = 0.00, P = .026), which might reflect a tendency to a faster symptom reduction in the FtF group and a lower score after twelve months. Employment status appeared to influence effect differently between the groups, were the B-CBT group was seen to profit more from not being full time employed than the FtF group. CONCLUSIONS Discussion: With large within-group effects in both treatment arms, the study demonstrated feasibility of B-CBT in Denmark. At six-months follow-up, there appeared to be no difference between the two treatment formats, with a small but non-significant difference at twelve months. The study seems to demonstrate that B-CBT is capable of producing treatment effects that are non-inferior to FtF-CBT and that completion rates and satisfaction rates were likewise non-inferior. However, the study was limited by small sample size and should be interpreted with caution. CLINICALTRIAL ClinicalTrials.gov NCT02796573 INTERNATIONAL REGISTERED REPORT RR2-http://dx.doi.org/10.1186/s12888-016-1140-y